-29-(-31)=x/11

Simple and best practice solution for -29-(-31)=x/11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -29-(-31)=x/11 equation:


x in (-oo:+oo)

31-29 = x/11 // - x/11

31-(x/11)-29 = 0

2-1/11*x = 0 // - 2

-1/11*x = -2 // : -1/11

x = -2/(-1/11)

x = 22

x = 22

See similar equations:

| 9-4k=7 | | -2/3-2+4/7 | | 6x-147=33 | | -5b-2=-4b+8-3b | | x^2+6x+69=0 | | 30=w+8 | | b^2*h^5*x/e^4*r=t^3*k/y | | -6x-7/3=4/5x-5/3 | | 4y/9=32 | | 9XM=10X-19X | | 2x(5+3x)=12 | | 4a=8-(a+7) | | 16+7k=8k+7k | | 4(-2-4K)=-7.8-15K | | 3.50+5.50+6x=51 | | A-17=10 | | 1/3y-1=-3/2y+7/3 | | log(2x^2+x)-2logx=2 | | 3=5/7x+1/7 | | 4x^3-2x+23x=3 | | (3x+5)(x+7)=90 | | 18+5x=180 | | Y=2/3x2+1 | | -6/5u+4/5=-1/2u-1 | | 1/4(2x-6)=4 | | -4(5x-6)+8x=3(x+7) | | 4x^3-2x+23=3 | | 3+8x=3x*2(x-1) | | 6*1=4 | | in(2x^2+x)-2inx=2 | | 10-3j=4 | | -1/3v-4/3=4v+2/5 |

Equations solver categories